2013
DOI: 10.1371/journal.pone.0061250
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Polymorphisms of miR-146a and miR-27a, H. pylori Infection, and Risk of Gastric Lesions in a Chinese Population

Abstract: BackgroundMicroRNAs (miRNAs) have been implicated in various human diseases. Single nucleotide polymorphisms (SNPs) in inflammation-related miRNA may play an important role in Helicobacter pylori (H. pylori)-induced gastric lesions. To evaluate the associations between miRNA SNPs, H. pylori and gastric lesions, a population-based study was conducted in Linqu County, China.Methodology/Principal FindingsBased on serum miRNA array conducted in this population, two SNP loci (miR-146a rs2910164: G>C and miR-27a rs8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…Song et al found that CC carriers of rs2910164 had a significantly increased risk of IM (OR - 1.42) and dysplasia (OR - 1.54) compared to GG carriers [12]. A similar observation was made in another study where combined effect of miR-146a (rs2910164) G/G and TLR4 SNP on the increased risk of severe AG among Japanese subjects was observed [18].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Song et al found that CC carriers of rs2910164 had a significantly increased risk of IM (OR - 1.42) and dysplasia (OR - 1.54) compared to GG carriers [12]. A similar observation was made in another study where combined effect of miR-146a (rs2910164) G/G and TLR4 SNP on the increased risk of severe AG among Japanese subjects was observed [18].…”
Section: Discussionsupporting
confidence: 53%
“…Another study showed a significantly increased risk of GC (OR - 1.48) for miR-27a SNP and further functional analyses indicated that variant genotypes might be responsible for elevated miR-27a levels and reduced ZBTB10 mRNA levels [16]. In contrast, a study including 2,380 participants with diverse gastric lesions did not find an increased risk of gastric IM or dysplasia for rs895819 [12]. A meta-analysis summarizing the findings of different case-control studies revealed that rs895819 polymorphism was significantly associated with decreased risks of cancer in white, but not in Asians [31].…”
Section: Discussionmentioning
confidence: 96%
“…Out of the Twenty-five, seven articles were pooled analysis, commentary and review papers (Wang et al, 2012;Yang and Burwinkel, 2012;Ma et al, 2013;Wang et al, 2013;Xu et al, 2013b;Zhong et al, 2013;Chen et al, 2014), and four reports were cancer biology experimental studies (Hirota et al, 2012;Jahid et al, 2012;Zanetti et al, 2012;Yuan et al, 2013). Three studies were excluded given that they did not include controls (Yoon et al, 2012;Xu et al, 2013a), or reported non-cancer disease (Song et al, 2013). We also included five eligible articles by manual searching (Li, 2011;Zhang, 2011;Zhang, 2012;Xu et al, 2013b;Kupcinskas et al, 2014), in which the study by Li et al included two independent case-control studies (Li, 2011) and the pooled analysis by Xu et al included one unpublished paper with efficient case-control study data (Xu et al, 2013b).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Among these are cytokine genes involved in the adaptive immune system [98,99,100] and pattern recognition factors initiating the innate immune system [101,102]. Furthermore, variation of genes encoding for proteases [103], xenobiotic metabolism enzymes [104], cell cycle regulators [105,106], mucins [107], HLA molecules [108], transcription factors [109], DNA repair enzymes [105,110,111], and micro-RNAs [112] has been reported to bear an increased risk for gastric cancer. Besides a ‘single gene' approach, also pathway-related pattern searches can be performed to allow a broader assessment of the pathobiological background [113].…”
Section: Host-related Factorsmentioning
confidence: 99%